Pendidikan Diniyah Formal - Ningamatuzzulfa, Alfi; Khurniyati; Sari, Widya Novita; Muzakky, Ahmad Faid; El Syam, Robingun Suyud (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2025)
Formal Diniyah Education (PDF) represents a systematic effort by the Indonesian government to recognize and integrate traditional pesantren religious education into the national education system. This study aims to synthesize and critically analyze various academic literatures regarding the philosophical foundations, regulatory frameworks, and curriculum implementation models of PDF since the enactment of related formal regulations. The method employed is library research with a qualitative content analysis approach toward policy documents, empirical research findings, and relevant scientific journal publications. Primary and secondary data sources were collected through online database searches and university repositories. The analysis results indicate a significant discourse regarding the challenges of synchronization between the universal goals of national education and the specific objectives of pesantren to produce Islamic scholars (tafaqquh fiddin). The study identifies that although the legal basis for PDF is robust, field implementation remains heterogeneous and depends on the local interpretation of the core curriculum by each pesantren. It is concluded that PDF has great potential as an integrated Islamic education model, but clearer standardization is needed concerning quality evaluation and graduate qualifications without eroding the autonomy and distinctiveness of the pesantren tradition.